-4q-(-18q)=-14

Simple and best practice solution for -4q-(-18q)=-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4q-(-18q)=-14 equation:


Simplifying
-4q + -1(-18q) = -14

Remove parenthesis around (-18q)
-4q + -1 * -18q = -14

Multiply -1 * -18
-4q + 18q = -14

Combine like terms: -4q + 18q = 14q
14q = -14

Solving
14q = -14

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Divide each side by '14'.
q = -1

Simplifying
q = -1

See similar equations:

| 4b+4b-7=25 | | 6a-1=2 | | 12=3(7-2) | | 2x-2x+2x+4x-5x=4 | | 4x+.5(8x-6)=2(4x+3) | | 0=12b-12 | | -5j+-16j+13j=16 | | 12=3(-2-2) | | h^2+b^2=8.5-h^2 | | x^2+y^2=8.5-h^2 | | 2c-(-6)=12 | | 5x-1+1x+15=6+5x+14-2x | | b+9=8+7 | | -6x-6(-3x)=-24 | | 2y+11=6-y | | (3k+1)x^2+2x=1 | | 7v+2(v-2)=-22 | | t*5-7=10 | | -5(2r+4)=10 | | -9x+-20x+19x+5x-(-9x)=-12 | | -6x+4x=14 | | 6t-3t-3t+3t=18 | | x*(x+1)+109=x+(x+1) | | 16t-15t=14 | | x=y-11 | | -3x-(-8x)=15 | | (8/125)-2/3 | | 5x-1+1x+15=6+5x+14-21 | | 19t-11t=16 | | -8x-7(-6x)=0 | | y=50+15x | | 9q-3q=6 |

Equations solver categories